Improving detection of carcinoma in situ in bladder cancer: urinary cytology vs the Xpert BC Monitor - Haas, Maximilian; Kriegmair, Maximilian; Breyer, Johannes; Sikic, Danijel; Wezel, Felix; Roghmann, Florian; Brehmer, Mirco; Wirtz, Ralph M.; Jarczyk, Jonas; Erben, Philipp; Bahlinger, Veronika; Goldschmidt, Franziska; et al. (BJU international, 2024)
Objective To investigate and compare the performance of urinary cytology and the Xpert BC Monitor test in the detection of bladder cancer in various clinically significant patient cohorts, including patients with carcinoma in situ (CIS), in a prospective multicentre setting, aiming to identify potential applications in clinical practice. Patients and Methods A total of 756 patients scheduled for transurethral resection of bladder tumour (TURBT) were prospectively screened between July 2018 and December 2020 at six German University Centres. Central urinary cytology and Xpert BC Monitor tests were performed prior to TURBT. The diagnostic performance of urinary cytology and the Xpert BC Monitor was evaluated according to sensitivity (SN), specificity (SC), negative predictive value (NPV) and positive predictive value (PPV). Statistical comparison of urinary cytology and the Xpert BC Monitor was conducted using the McNemar test. Results Of 756 screened patients, 733 (568 male [78%]; median [interquartile range] age 72?[62?79] years) were included. Bladder cancer was present in 482 patients (65.8%) with 258 (53.5%) high-grade tumours. Overall SN, SC, NPV and PPV were 39%, 93%, 44% and 92% for urinary cytology, and 75%, 69%, 59% and 82% for the Xpert BC Monitor. In patients with CIS (concomitant or solitary), SN, SC, NPV and PPV were 59%, 93%, 87% and 50% for urinary cytology, and 90%, 69%, 95% and 50% for the Xpert BC Monitor. The Xpert BC Monitor missed four tumours (NPV?=?98%) in patients with solitary CIS, while potentially avoiding 63.3% of TURBTs in inconclusive or negative cystoscopy and a negative Xpert result. Conclusion Positive urinary cytology may indicate bladder cancer and should be taken seriously. The Xpert BC Monitor may represent a useful diagnostic tool for correctly identifying patients with solitary CIS and unsuspicious or inconclusive cystoscopy.
Erstmals veröffenticht: 08. Mai 2024
Gesehen am 10.12.2024